EVALUATION OF HYDROPONIC FODDER PERFORMANCE OF DIFFERENT VARIETIES OF SORGHUM - Garuma, Zelalem; Gurmessa, Kassahun (International Journal of Research -GRANTHAALAYAH, 2021)
The hydroponic fodder yield performance evaluation of different varities of sorghum was conducted in green house of Wollega University.. Three experiments were conducted. The first was to observe effects of irrigation frequency. The second one was undertaken to evaluate four sorghum varieties (Lalo, Chemeda, Gamadi and Dano) on fodder yield, yield related components and nutritive values. The third experiment was done to determine the appropriate date of harvest for biomass yield and agronomic traits. Complete randomized design (CRD) was employed to conduct the experiment with three replications. The results showed that there was no significant difference (p>0.05) between treatments on Dry matter yield (t/ha), Leaf Weight (t/ha), Root weight (t/ha) and Plant height (cm) as effect of frequency of watering at 2hr, 3hr and 4hr interval but, significant difference (p<0.05) among varieties of sorghums as an effect of frequency of irrigation on Fresh yield(t/ha), Plant height (cm) and leaf to root ratio (LRR%).The lowest average fresh yields were harvested at 7th days after planting and consistently increased until 17th days of planting. The highest plant heights were observed at 17 days while the lowest was observed at 7th days of harvesting. Except for dry matter (DM), Ash and crude protein (CP), there were significant differences (P<0.05) in neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL) and in vitro dry matter digestibility contents of the sorghum varieties. The Sorghum variety, Gamadi contained the highest CP (13.29%) and lowest Acid detergent lignin contents. The Sorghum variety, Chemeda showed best in vitro DM digestibility (73.24%). Harvesting hydroponic sorghum at 17 days after planting gave the best biomass yield (t/ha), LRR and Plant height (cm); showing the increase in biomass as time of harvesting increases. Among the tested varieties of sorghum a variety, Dano best for biomass yield among the others.